Partitioning of gross energy intake and metabolizable energy supply in bovines F1: Energy partitioning in bovines - Vázquez-Carrillo, María Fernanda; Montelongo-Pérez, Hugo Daniel; González-Ronquillo, Manuel; Castillo-Gallegos, Epigmenio; Castelán-Ortega, Octavio Alonso (Ecosistemas y Recursos Agropecuarios, 2021)
The partition of the gross energy intake (GEi) by heifers, the energy density, metabolicity of the diet (qm), and the Ym factor were estimated, by the open circuit respiration chamber technique. Four heifers of 206 ± 39.7 kg of live weight and 12 ± 0.93 months of age were used in a completely randomized design. The heifers were randomly assigned to two diets: Diet A consisted of 74% corn silage + 26% commercial concentrate and diet B 100% corn silage. A t-test was used for analysis of results. Dry matter intake (DMI), digestibility of the DM, Ym factor and methane yield (CH4 g kg−1 DMI) for both diets were different (P < 0.05). In the present study we were able to estimate the partitioning of the GE consumed by the experimental animals; as well as the energy density, the Ym and qm factors of the diet.